Peluang dan Tantangan Financial Technology (Fintech) dalam Sistem Pembayaran Berbasis QRIS Pada UMKM di Kecamatan Medan Kota - Sahdila Putri; Radiman Radiman (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine the opportunities and challenges of Financial Technology (Fintech) in a QRIS-based payment system for MSMEs in Medan Kota District. The research method used in this study is a descriptive qualitative research method with an empirical approach. The results of research on 30 UMKM show that Fintech Opportunities in a QRIS-based payment system create sales revenue for MSMEs through collaboration with Fintech in a QRIS-based payment system which can market these products to E-commerce that has collaborated such as Grab, Gojek, Shopeefood and other. This QRIS payment is very practical, with one scan, the payment process has been completed and is done with only one barcode. Its strengths are facilitating service access, facilitating transactions, avoiding counterfeit money, no need to provide cash and automatic recorded transactions. Meanwhile, the challenges of Fintech in the QRIS-based payment system with current technological developments have made the community meet their daily needs with all-digital means and help SMEs in marketing their products online. However, there is still a lack of understanding in the use of these technologies which is one of the problems in this progress. As for the number of technological crimes that make users more vigilant. For MSMEs, the existence of QRIS payments is very beneficial for them, but it is weighed down by the admin fees that are borne by merchants not borne by consumers, called the MDR (Merchant Discount Rate) of 0.7%. The weakness is that it depends on the internet network and smartphone ownership which is not evenly distributed for the whole community.